EXPLORING THE ROLE OF APPLIED THEATRE AND EXPRESSIVE ART THERAPY IN VICTIM RECOVERY: A REVIEW - Karayil, Amrutha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
After experiencing trauma, individuals often face psychological distress that conventional talk therapy may not fully address. Alternative and complementary therapeutic approaches such as Applied Theatre (AT) and Expressive Art Therapy (EAT) have been explored for their potential to assist in healing, empowerment, and reintegration. These creative interventions focus on embodied expression, narrative reconstruction, and participatory engagement, providing individuals an opportunity to process their experiences through non-verbal and symbolic forms. This review aims to investigate the role of AT and EAT in recovery from trauma, particularly trauma caused by violence, abuse, displacement, and disaster. By synthesizing findings from interdisciplinary research, this paper evaluates the efficacy, methodologies, and outcomes of these interventions in various cultural and institutional contexts with special focus on transitional justice and gender based violences.